Interactively Mapped Holodomor Oral History: Geoinformation Systems Serve History - Boriak Tetiana (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2022)

(untitled)
The author proposes the results of her many-year research in preparation the database for a module of an interactive map of the Holodomor of the Project Mapa. Initially geoinformation (GIS) technologies began to be used in agriculture, administration, geodesy, sociology, demography. Eventually these approach began to be used in history. Ukrainian historians have been implementing GIS into their researchs and to applyit to study number of topics. These are: the projects launched by Ukrainian Institute of National Memory (was not completed), the National Museum of the Holodomor-Genocide (Museum), L’viv Section of the Institute of Archeography. The projects of the two latter institutions seem to be in progress (places of mass burial of the Holodomor victims; Ukrainian victims of Volhynia and towns of Belz voievodship of 15 - 17 thcenturies). Mapa project began to be elaborated from the beginning of the 2010 s. Initially it was planned to be the resource for representation of demographic and economic data. Gradually the project was broadened to include oral history. Now Mapa includesa set of interactive maps, divided into two groups: Historical atlas (the Great Famine module as a part of it) and Contemporary Atlas (includes 10 modules). The author has selected 5 thematic sections: confiscation of food and cattle; cannibalism; resistance; strategies for survival; feeding in a collective farm/village. The article provides explanations for every group and ties to them. 19 printed and online sources has become the source for the map. Considering impossibility to include into the map all data available, the module Testimonies allows seeing amount of cases in selected five groups, making estimation on higher levels.